Transitional vertebrae and numerical variants of the spine: prevalence and relationship to low back pain or degenerative spondylolisthesis. (1st July 2021) - Sugiura, Kosuke; Morimoto, Masatoshi; Higashino, Kosaku; Takeuchi, Makoto; Manabe, Akihiro; Takao, Shoichiro; Maeda, Toru; Sairyo, Koichi
Abstract : Aims: Although lumbosacral transitional vertebrae (LSTV) are well-documented, few large-scale studies have investigated thoracolumbar transitional vertebrae (TLTV) and spinal numerical variants. This study sought to establish the prevalence of numerical variants and to evaluate their relationship with clinical problems. Methods: A total of 1, 179 patients who had undergone thoracic, abdominal, and pelvic CT scanning were divided into groups according to the number of thoracic and lumbar vertebrae, and the presence or absence of TLTV or LSTV. The prevalence of spinal anomalies was noted. The relationship of spinal anomalies to clinical symptoms (low back pain, Japanese Orthopaedic Association score, Roland-Morris Disability Questionnaire) and degenerative spondylolisthesis (DS) was also investigated. Results: Normal vertebral morphology (12 thoracic and five lumbar vertebrae without TLTV and LSTV) was present in 531 male (76.7%) and 369 female patients (75.8%). Thoracolumbar transitional vertebrae were present in 15.8% of males and 16.0% of females. LSTV were present in 7.1% of males and 9.0% of females. The prevalence of the anomaly of 16 presacral mobile vertebrae (total number of thoracolumbar vertebrae and TLTV) without LSTV was 1.0% in males and 4.1% in females, and that of the anomaly of 18 vertebrae without LSTV was 5.3% in males and 1.2% in females. The prevalence of DS was significantly higher in females with a total of 16 vertebrae than in those with normal morphology. There was no significant correlation between a spinal anomaly and clinical symptoms. Conclusion: Overall, 24% of subjects had anomalies in the thoracolumbar region: the type of anomaly differed between males and females, which could have significant implications for spinal surgery. A decreased number of vertebrae was associated with DS: numerical variants may potentially be a clinical problem. Cite this article: Bone Joint J 2021;103-B(7):1301–1308.